Knowledge and Information-Seeking Behaviour on Nasopharyngeal Cancer in Urban and Rural Sarawak, Malaysia - Ting, Su Hie; Podin, Yuwana (Global Academy of Training & Research (GATR) Enterprise, 2019, 2019)
The study examined knowledge and information-seeking behaviour on nasopharyngeal cancer (NPC) in urban and rural Sarawak. A survey was conducted in Kuching and Kampung Bengoh involving 121 respondents (44 Kuching; 77 Kampung Bengoh). The results showed that most respondents do not have family and friends who had NPC, and their work are not related to NPC. A majority of them had not looked for information on NPC and only four of them have had screening for NPC. As for intention to obtain more information on NPC in the next six months, only 46.3% reported likelihood to do so but 20.7% were unlikely to do so because they felt uncomfortable with the subject of cancer and they did not feel a need to find out more about it. There were no significant differences between the Kuching and Bengoh respondents on their attitudes towards information-seeking on cancer and intention to seek information on NPC. However, the common sources of information on NPC differ for the urban and rural respondents: the urban respondents relied on the Internet, their doctors and leaflets for NPC information but the rural respondents depended on the television, radio and newspaper are the main sources of health information. These results suggest that different channels of information need to be used to address the low level of awareness on NPC and ambivalent attitudes towards seeking information on NPC in rural and urban areas in Sarawak.